Leguminosae Lectins as Biological Tools in Medical Research: a Review - Barbosa,Paula Perazzo de Souza (2021)
Abstract Lectins were discovered first in plants and later in other living things, and nowadays it is known that they are present in almost all many life forms. These proteins can bind to specific carbohydrates, which make them perform a number of biological activities and can be used as tools in the study of glycoconjugate structures present on the cell surface, being effective in medical research. Plant lectins, leguminosae lectins particularly, are among the most studied plant proteins. They are very versatile molecules, which show several interesting biological properties. Thus, the present paper reviewed the advances about the leguminosae lectins biological properties studies in the last ten years, taking into account their possible applications in the fields of Clinical Microbiology, Pharmacy and Cancerology through a search in the electronic databases, providing opportunity to exchange information about the theme. Leguminosae lectins can neutralize pathogenic organisms, be they viruses, prokaryotes and eukaryotes, in addition carcinogenic cells, besides decreasing oxidative stress, conditions which increases the possibility of alternative substances for the design of new drugs to be used in current therapeutic, expanding the possibilities of diseases cure.